EKSPERIMENTASI MODEL PEMBELAJARAN ROUNDTABLE (RT) DAN QUESTION STUDENT HAVE (QSH) DENGAN PENDEKATAN SAINTIFIK PADA MATERI OPERASI BENTUK ALJABAR DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMP SE-KOTA METRO LAMPUNG TAHUN PELAJARAN 2014/2015 - Widyaningrum, Amalia Zulvia; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2015)
Abstract: This research aimed to find out: (1) which one is better among learning models of RT with scientific approach, QSH with scientific approach or classical with scientific approach one in giving mathematics learning achievement, (2) which one is better among studentsâ learning styles, students having visual, auditorial or kinesthetic giving mathematics learning achievement. (3) in each learning model, which one is better among studentsâ learning styles in giving mathematics learning achievement and (4) in each learning styles, which one is better among RT with scientific approach, QSH with scientific approach or classical with scientific approach in giving mathematics learning achievement. This research was the quasi-experimental research with 3Ã3 factorial design. The population of research was all grade VIII students of Junior High School (SMP) in Metro, Lampung. The samples were chosen by using stratified cluster random sampling. The instruments that were used to collect the data were the test of mathematics achievement and questionnaire of learning styles. As a requirement of research, both of the instruments should be measured.Â  Test of studentsâ learning achievement data was measured by using content validity, level of difficulty, discrimination power and reliability. Questionnaire data were examined by using content validity, internal consistency and reliability. Pre-requisite tests were used Lilliefors method for normality test and Bartlett method for homogeneity test. After examining the data, it shows that the populations have same variance and they were in normal distribution. Prior knowledge data are examined by using one-way ANOVA with unbalanced cells. It shows that three classes have balance prior knowledge. Meanwhile, the technique of analyzing the data was two-ways ANOVA with unbalanced cells. The result of research showed as follows. (1) The RT with scientific approach had better learning achievement than the QSH and classical with scientific approach. QSH with scientific approach provided better learning achievement than the classical with scientific approach, (2) The students having visual learning style had learning achievement as good as those having auditorial learning style. The students having visual learning style had better learning achievement than did those having kinesthetic learning style. The students having auditorial learning style had learning achievement as good as those having kinesthetic learning style. Â (3) In each of learning styles, studentâs mathematics learning achievement is in constancy with result of learning models (4) In each learning models, the studentâs mathematics learning achievement is in constancy withÂ  result of learning style categories.Keywords: Round Table (RT), Question Student Have (QSH), Classical, Â Learning Style